The Impact of Social Protection on Community Resilience in the Context of Climate Change and Natural Disaster - Fahrudin, Adi; Andayani, Rini Hartini Rinda; Albert, Wanda Kiyah George; Hindarsah, Ida; Hakim, Moch Zaenal; Yusuf, Husmiati (Journal of Ecohumanism, 2024)
This review article examines the role of social protection programs in strengthening community resilience in the face of climate change and natural disasters. Through a review of literature and case studies in the Asia-Pacific region, the article highlights how integrating risk-informed strategies into the design of social protection programs can reduce community vulnerability and improve their ability to recover from shocks. Programs such as cash transfers, weather-index insurance, and public works have been shown to help vulnerable households cope with disasters. The article also emphasizes the importance of flexibility in social protection program design, enabling a rapid response to disasters. Finally, it offers policy recommendations to enhance the effectiveness of social protection programs in building resilience against the impacts of climate change.